How does cultivar, maturation, and pre-treatment affect nutritional, physicochemical, and pasting properties of plantain flours? - Udomkun, Patchimaporn; Masso, C.; Swennen, Rony L.; Innawong, B.; Alakonya, A.; Fotso Kuate, A.; Vanlauwe, Bernard (MDPI, 2021)
The effect of cultivar, ripening stage, and pre-treatment method were investigated on the nutritional, physicochemical, and pasting properties of plantain flours from two plantains and two plantain hybrids. There were significant variations (p < 0.05) in chemical composition and physical properties influenced by the interaction of cultivars, ripening stages, and pre-treatment methods. The highest levels of amylose, water-holding capacity (WHC), and oil-holding capacity (OHC) were observed in unripe flours and acid-treated flour recorded the highest content of resistant starch (RS). Flour after pre-blanching contained the highest level of total phenolic (TP), carotenoid contents, and browning index (BI) value. In contrast, acid-treated flours had the lowest BI value. As ripening progressed, peak viscosity and breakdown values increased but final viscosity, setback, and pasting temperature values were reduced. Untreated flour samples showed the highest peak viscosity. Higher breakdown values were found in acid-treated samples and higher setback values in pre-blanched samples.